Mechanisms of digital technology in establishing the quality of scientific research - Lallouche, Samira (Journal of Humanities & Social Sciences, 2023)
The study aimed to know the importance of digital technology and its impact on establishing the quality of scientific research as one of the most important vital methods adopted in the learning process, especially in a time of speed and knowledge explosion in various fields. The study used the scientific method, which is based on description and analysis, to identify the objectives of the study. The research community included the basics and standards for the quality of scientific research and the role of digital technology in improving the quality of scientific research and its impact on the credibility of the research, while identifying the disadvantages of adopting digital technology and ways to overcome them. In light of the foregoing, the study reached several results, the most important of which is that digital technology has the advantage of delivering information to the recipient and supporting the researcher in the education process, as it encouraged him to produce distinguished and innovative scientific research. In addition, to implement a clear strategy for investing digital technology in the field of scientific research, important steps must be taken, represented in the need for full awareness of modern digital trends and their importance in various disciplines. And the establishment of specialized research centers supervised by specialized experts who study the reality of technology in scientific research and ways to develop scientific research in it. In light of the results, the study recommends the need to establish a digital technological park and continue to form the digital infrastructure for the preparation of digital educational programs, and the need to work on organizing training programs for faculty members and developing them professionally in order to employ technology in the education process.